Knowledge, attitudes, and practices regarding Dengue fever among the students of Jaffna University - Sivamainthan, S.; Gowthamy, Y.; Coonghe, P. A. D.; Murugananthan, K. (University of Jaffna, 2024)
Dengue fever is recognized as the most common mosquito-borne viral disease in recent decades and is one of the world’s emerging infectious diseases. Epidemiological data from Sri Lanka showed a gradual increase in morbidity and mortality from 2009 to 2019. Preventive measures are crucial in controlling and limiting the spread of mosquito vectors. This study aimed to evaluate the knowledge, attitudes, and practices (KAP) regarding Dengue fever among university students of Jaffna. A descriptive cross-sectional study was conducted among firstyear students at the University of Jaffna in August 2019. Stratified random sampling was used, and data were collected using a self-administered questionnaire. Ethical clearance was obtained from, Faculty of Medicine, University of Jaffna. Each participant's KAP regarding dengue fever (DF) were individually scored out of 100. A score of 75 and above was classified as 'good' KAP, scores between 50 and 74 as 'average,' and scores below 50 as 'poor’. Descriptive data were analyzed using Pearson’s chi-squared test, with a p-value of less than or equal to 0.05 considered significant. Among the participants, 74%, 99.6%, and 60.8% demonstrated satisfactory KAP regarding dengue fever, respectively. Students of Faculty of Management studies and commerce showed the highest percentage of above-average knowledge (93%), followed by students of Faculty of agriculture (87.5%) and students from Faculty of Medical students (85.7%). Among the faculties, 100% of students had above-average attitudes (p=0.008) except Faculty of sciences. Additionally, 86% of Students from Faculty of Management studies and Commerce had above-average level of practice (p = 0.001). This study revealed that all the undergraduate students had better attitudes regarding dengue fever. Although over half of the participants demonstrated satisfactory levels of knowledge and practices, significant gaps still remain. Greater emphasis should be placed on improving knowledge and practices among undergraduate students at the University of Jaffna.
Keywords: Dengue; Knowledge; Attitude; Practice; University students